Evaluating the Efficacy of Preemptive Intraincisional Infiltration of Magnesium Sulfate on Postoperative Pain in Cesarean Section under Spinal Anesthesia - Mitra Jabalameli; Seyed Mahmood Hashemian; Azar Danesh-Shahraki; Mansoureh Zarin-Makan (مجله دانشکده پزشکی اصفهان, 2017)
Background: Inadequate pain control has a significant role in maternal and neonatal health in the early postpartum period. It interferes with breastfeeding and has a negative influence on child normal growth. This study aimed to evaluate the preemptive effect of intraincisional infiltration magnesium sulfate on postoperative pain control.